2009
DOI: 10.1039/b821041a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, in vivo antitumor properties of the cluster rhenium compound with GABA ligands and its synergism with cisplatin

Abstract: A new dirhenium(III) complex cis-[Re2(GABA)2Cl5(H2O)]Cl.2H2O with zwitterionic gamma-aminobutyrate ligands was prepared and characterized by spectral methods and crystallography. The structure of the compound is comprised of dinuclear complex cations (Re-Re 2.2437(3) A) involving cis-oriented double carboxylate bridges, four equatorial chloride ions and two weakly bonded aqua and chloride ligands in the axial positions at two rhenium centers (Re-O 2.363(3), Re-Cl 2.6735(12) A). Antitumor properties of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 32 publications
1
69
0
6
Order By: Relevance
“…This was demonstrated in animal models with tumor-bearing rats, as was a synergism between cisplatin and Re (III) diadamantate (22) and with dichlorotetra-μ-isobutyratodirhenium (III) complex (23) and the cluster Re compound with gamma-aminobutyric acid ligand (24). This synergism was however not observed with the Re (I)-diselenoether complex (4,3), but the schedule of treatments were different.…”
mentioning
confidence: 88%
“…This was demonstrated in animal models with tumor-bearing rats, as was a synergism between cisplatin and Re (III) diadamantate (22) and with dichlorotetra-μ-isobutyratodirhenium (III) complex (23) and the cluster Re compound with gamma-aminobutyric acid ligand (24). This synergism was however not observed with the Re (I)-diselenoether complex (4,3), but the schedule of treatments were different.…”
mentioning
confidence: 88%
“…-Earlier, a dirhenium cluster compound with propanoate ligands was found to be active against some types of cancer [12]. These investigators and, later, we [4] found that such compounds decomposed readily into insoluble Re oxides, found in high quantities in the peritoneal cavity of experimental animals, therefore, requiring a considerable amount to be injected so that any significant quantity can reach tumor sites. Use of liposomal forms of dirhenium cluster compounds allowed us to overcome these disadvantages and to elaborate a rather effective antitumor therapy [4] [13].…”
mentioning
confidence: 95%
“…4, C) [54]. This may find further applications for the development of new antitumor dirhenium(III) species with active ligands.…”
Section: Fig 3 Volumes Of Tumors In Experiments Withmentioning
confidence: 99%
“…The description of our experiments is also presented, details you may find in [44,49,[53][54][55][56].…”
Section: Anticancer Activity Of Dirhenium Clusters and Work Of The Rhmentioning
confidence: 99%
See 1 more Smart Citation